Smart Health Monitoring and Management System for Organizations Using Radio-Frequency Identification (RFID) Technology in Hospitals or Emergency Applications - Yaw-Wen Kuo; Yung-Chung Tsao; Web-Chang Chien; Yuh-Ming Huang; Lun-De Liao (Emergency Medicine International)
In the public health domain, healthcare systems are a crucial part of the economy, transportation, education, health infrastructure, and military of any country. In this study, a system is proposed to implement smart people management, monitoring, and tracking processes that can be used in hospitals to automate and organize information management. For disease management in a public setting, measuring forehead temperatures is a standard method of identifying people for further treatment. To prevent disease transmission on campuses or in any public space, daily temperature checks for everyone have been mandated at the entrances to many public spaces. Although this task can be performed in seconds for an individual, substantial human resources are required to perform temperature checks for all people arriving at one or more specified checkpoints each day during an epidemic. As a result, a smart measuring, monitoring, and management system is urgently needed. We propose a complete solution that includes current Internet of Things technology that can be used in hospitals or any public space to automate and organize information management operations. This system offers a cost-effective means of enhancing reliability, privacy, and security for healthcare record management. One attractive feature of the system is its low cost due to the use of off-the-shelf devices and sensors that can be sourced and operated in our region. Recorded measurements of vital sig/ns are presented via a compact, user-friendly interface that can be monitored remotely. Because the proposed solution is based on mature existing hardware modules and software packages, any experienced information technology professional can quickly build an analogous monitoring and management system by following the instructions presented in this paper.